Pirate Adventure - Hunt, Roderick, 2012; Roderick Hunt, 1986; Alex Brychta, 1986 (Oxford University Press UK, 2012)
The document summarizes a children's storybook about three friends, Biff, Chip, and Wilf, who discover a magic key that transports them into a miniature pirate-themed world inside a toy house. At first scared by the pirates, the children eventually have fun playing at the pirate party. By the end of their magical adventure, even Biff, who did not like pirates at first, has changed her mind and had a good time.
This book is designed to take children who need help in their reading to Stage 5 using earlier Oxford Reading Tree key words and words that occur frequently.
H3
Emergent to early fluent readers. Children beginning to read with more confidence. Can decode CVC words and some irregular sight words. Beginning to read with phrasing and comprehension
Keywords: Supplementary reading material